Amyloidosis in Retinal Neurodegenerative Diseases - Masuzzo, Ambra; Dinet, Virginie; Cavanagh, Chelsea; Mascarelli, Frederic; Krantic, Slavica (Frontiers in Neurology, 2016)
As a part of the central nervous system, the retina may reflect both physiological processes and abnormalities related to pathologies that affect the brain. Amyloidosis due to the accumulation of amyloid-beta (Aβ) was initially regarded as a specific and exclusive characteristic of neurodegenerative alterations seen in the brain of Alzheimer’s disease (AD) patients. More recently, it was discovered that amyloidosis-related alterations, similar to those seen in the brain of Alzheimer’s patients, also occur in the retina. Remarkably, these alterations were identified not only in primary retinal pathologies, such as age-related macular degeneration (AMD) and glaucoma, but also in the retinas of Alzheimer’s patients. In this review, we first briefly discuss the biogenesis of Aβ, a peptide involved in amyloidosis. We then discuss some pathological aspects (synaptic dysfunction, mitochondrial failure, glial activation, and vascular abnormalities) related to the neurotoxic effects of Aβ. We finally highlight common features shared by AD, AMD, and glaucoma in the context of Aβ amyloidosis and further discuss why the retina, due to the transparency of the eye, can be considered as a “window” to the brain.